Spatial and temporal expression of alpha- and beta-thyroid hormone receptor mRNAs, including the beta 2-subtype, in the developing mammalian nervous system - Bradley, DJ (J Neurosci, 1992)
Thyroid hormone exerts profound effects on the developing mammalian brain, and its deficiency can lead to severe mental retardation and motor abnormalities. To identify specific anatomic targets of thyroid hormone action in the developing mammalian nervous system, we examined thyroid hormone receptor gene expression by hybridization histochemistry on serial adjacent sections from 12 stages of the developing rat nervous system. 35S-labeled cRNA probes were generated from divergent sequences of rat alpha 1-, alpha 2-, beta 1-, and beta 2- thyroid hormone receptor and related cDNAs. We found that alpha- and beta-thyroid hormone receptor genes have distinct patterns of spatiotemporal expression in the embryonic and postnatal rat nervous system. alpha 1- and alpha 2-mRNAs were widely expressed in similar patterns; highest levels were found in the fetal neocortical plate, site of cortical neuronal differentiation. In contrast, beta 1- transcripts were restricted in distribution, with prominent expression in zones of neuroblast proliferation such as the germinal trigone and the cortical ventricular layer. Surprisingly, the “pituitary-specific” beta 2-transcript was detected in the developing hippocampus and striatum. Our results suggest that alpha- and beta-thyroid hormone receptors may play distinct functional roles during development of the mammalian nervous system.